PENA PRIVATIVA DE LIBERDADE NO BRASIL - Sellito, Adriele; Alencar, Daniely Cristina de Souza; Silva, Joseano Nunes da; Nunes, Lucilene Barbosa; Rocha, Patricia Feu da; Marques, Rafael Ramos; Eleotério, Renata Pereira Garola; Junior, Roberto Roggiero; Macena, Lincoln Villas Boas (Revista Ciências Jurídicas e Sociais - UNG-Ser, 2014)
...ver texto na íntegra.